2018
DOI: 10.1016/j.ijfatigue.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network for random fatigue loading analysis including the effect of mean stress

Abstract: The effect of mean stress is a significant factor in design for fatigue, especially under high cycle service conditions. The incorporation of mean stress effect in random loading fatigue problems using the frequency domain method is still a challenge. The problem is due to the fact that all cycle by cycle mean stress effects are aggregated during the Fourier transform process into a single zero frequency content. Artificial neural network (ANN) has great scope for non-linear generalization. This paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…The training, validation and testing process followed in this work is similar to those in previous works by the author and colleagues [30,31,43]. Generally, the feed forward backpropagation multilayer perceptron (MLP) model was followed.…”
Section: Training Validation and Testing Of The Ann Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…The training, validation and testing process followed in this work is similar to those in previous works by the author and colleagues [30,31,43]. Generally, the feed forward backpropagation multilayer perceptron (MLP) model was followed.…”
Section: Training Validation and Testing Of The Ann Modelsmentioning
confidence: 97%
“…The input parameters considered are presented in section 4.2. The number of hidden layer used was 25 as in previous studies [30,31]. This number was found to be adequate by checking the residual error and goodness of fit of the ANN prediction with target results.…”
Section: Ann Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The maintained level of deviations in the plot proves it to be normalized from higher deviations of data 29 . The higher mean square error value is due to the lower samples of data 30 . The decrease in the mean square error value also proves the working of feed-back gradient descent optimization mechanism of algorithm, through which the parameters are made to fit into the model correctly by improving the weight of the input data 31 .…”
Section: Mean Square Errormentioning
confidence: 99%
“…KhudariBek et al indicated that the overall elastic modulus of Nanocomposite material increases with the volume fraction of nano-particles and inter-phase thickness [11]. According to J F Durodola et al greater resolution was observed with the artificial neural network method than with other available methods that include the effect of mean stress on the frequency domain approach and predict the fatigue damage [12]. Aparna Gangele et al mentioned in the report that the FEM model shows that the single layer graphene helps to enhance the mechanical properties of silicon nanosheets, which is helpful for the silicon-based semiconductor industry [13].…”
Section: Introductionmentioning
confidence: 99%